How informative are central bank assessments of macroeconomic risks? - Malte Knüppel; Guido Schultefrankenfeld (Deutsche Bundesbank, 2011)
Surveying the forecasting practice of several central banks, we find that all these banks issue statements about risks to their macroeconomic forecasts. Often the balance of these risks is assessed as well. Upward [downward] risks to the forecast commonly imply that the outturn is expected to lie above [below] the central forecast. Investigating the inflation risk forecasts of the Bank of England and the Sveriges Riksbank, however, we do not find conclusive evidence for informativeness, that is, for a systematic connection between risk assessments and forecast errors. Thus, it seems questionable whether macroeconomic risk forecasts are meaningful.
Keywords: E37; C12; C53; 330; forecast evaluation; risk forecasts; inflation forecasts